Антидисбиотическое действие мукозальных фитогелей на слизистую оболочку полости рта крыс при экспериментальном сахарном диабете 2 типа = Antidysbiotic action of mucosal gels on rats oral cavity mucosa at experimental diabetes of type 2 - Skiba, A. V.; Hromagina, L. N.; Skiba, V. Y. (Journal of Education, Health and Sport, 2015)
Skiba A V, Hromagina L N, Skiba V Y. Антидисбиотическое действие мукозальных фитогелей на слизистую оболочку полости рта крыс при экспериментальном сахарном диабете 2 типа = Antidysbiotic action of mucosal gels on rats oral cavity mucosa at experimental diabetes of type 2. Journal of Education, Health and Sport. 2015;5(2):326-332. ISSN 2391-8306. DOI 10.5281/zenodo.17887 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A326-332 https://pbn.nauka.gov.pl/works/561504 http://dx.doi.org/10.5281/zenodo.17887 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. УДК (612.084+577.15):616.379-008.64 АНТИДИСБИОТИЧЕСКОЕ ДЕЙСТВИЕ МУКОЗАЛЬНЫХ ФИТОГЕЛЕЙ НА СЛИЗИСТУЮ ОБОЛОЧКУ ПОЛОСТИ РТА КРЫС ПРИ экспериментальном САХАРНОМ ДИАБЕТЕ 2 ТИПА ANTIDYSBIOTIC ACTION of mucosal gels ON RATS oral cavity mucosa AT EXPERIMENTAL diabetes OF TYPE 2 А. В. Скиба, Л. Н. Хромагина, В. Я. Скиба A V Skiba, L N Hromagina, V Y Skiba ГУ «Институт стоматологии НАМН Украины» SE "The Institute of Stomatology of NAMS of Ukraine» ABSTRACT In patients with diabetes in the body conditions are created conducive to the development of dysbiosis, including oral cavity. The increase in microbial contamination, changing of associative interactions, increased reproduction of unusual for a healthy oral cavity bacteria leads to the development of pathological processes as candidosis, stomatitis, periodontitis. The aim of research was a comparative study of the phyto gel effectiveness possessing anti dysbiotic action in the oral cavity of rats in the modeling of diabetes. Materials and methods. In the study was used white Wistar rats, in which was reproduced type 2 diabetes using protamine. Phyto gels contain: lysozyme, quercetin, grape flour and blueberries extract. Results of the study. Conclusions. In modeling of type 2 diabetes in oral cavity mucous membrane significantly increased urease activity and sharply reduced lysozyme activity, developing dysbiosis. Oral application of various photo gels provided antidysbiotic effect on the buccal and tongue mucosa of rats to varying degrees. Keywords: diabetes mellitus, dysbiosis, oral cavity mucosa, oral phyto gels. РЕФЕРАТ При моделировании у крыс сахарного диабета 2 типа в слизистой полости рта развивался дисбиоз, определяемый по соотношению активностей уреазы и лизоцима. Оральные аппликации фитогелей, содержащих лизоцим, кверцетин, муку из виноградных листьев или водный экстракт ягод черники, оказывают антидисбиотическое действие, причем, на слизистую щеки в большей степени черника, а на слизистую языка виноград и кверцетин. Ключевые слова: сахарный диабет, дисбиоз, слизистая полости рта, оральные фитогели.